The Differences in the Flavan-3-ol and Procyanidin Contents of the Japanese ‘Fuji’ and ‘Orin’ Apples Using a Rapid Quantitative High-Performance Liquid Chromatography Method: Estimation of the Japanese Intake of Flavan-3-ols and Procyanidins from Apple as Case Study - Shoji, Toshihiko (Foods, 2021)
Previously, we reported that apple polyphenols and their major active compounds, the flavan-3-ols and the procyanidins, can result in various health benefits in animals and humans, according to clinical studies. Here, we developed a rapid method for quantifying flavan-3-ols and procyanidins using high-performance liquid chromatography with fluorescence detection, where we investigated the amounts of flavan-3-ols and procyanidins in the Japanese major apple production centre, the Aomori Prefecture, from 2016 to 2018. The non-bagged ‘Fuji (n = 609)’, the bagged ‘Fuji (n = 1101)’, and the ‘Orin (n = 504)’ apples were evaluated in terms of their differences in flavan-3-ols and procyanidins based on apple variety and the controlled atmosphere storage. The bagging treatments of the ‘Fuji’ apples resulted in significantly higher concentrations of procyanidins, while changes in flavan-3-ols concentrations were not clearly observed by treatment. In addition, ‘Orin’ had a significantly higher concentration of procyanidins than that of ‘Fuji’. In contrast, the controlled atmosphere storage hardly caused any changes in the flavan-3-ol and procyanidin contents. Hence, we present the concentrations of flavan-3-ols and procyanidins in major Japanese apples using the rapid high-performance liquid chromatography method with fluorescence detection.